Synthesis of vulcanite (CuTe) and metastable Cu1.5Te nanocrystals using a dialkyl ditelluride precursor. Issue 45 (11th November 2020) - Robinson, Evan H.; Dwyer, Kaelyn M.; Koziel, Alexandra C.; Nuriye, Ahmed Y.; Macdonald, Janet. E.
Abstract : A unique ditelluride precursor enables nanoscale access to vulcanite nanosheets and metastable cube-like Cu1.5 Te nanocrystals. Abstract : This study demonstrates that a dialkyl ditelluride reagent can produce metastable and difficult-to-achieve metal telluride phases in nanocrystal syntheses. Using didodecyl ditelluride and without the need for phosphine precursors, nanocubes of the pseudo-cubic phase (Cu1.5 Te) were synthesized at the moderate temperature of 135 °C. At the higher temperature of 155 °C, 2-D nanosheets of vulcanite (CuTe) resulted, a nanomaterial in a phase that has not been previously achieved through thermal decomposition methods. Materials were characterized with TEM, powder XRD and UV-Vis-NIR absorbance spectroscopy.